Life quality change after inflatable penile prosthesis implantation. (4th December 2020) - Ure, Iyimser; Ozen, Ata; Can, Cavit
Abstract: Purpose: It was aimed to evaluate the changes in quality of life in patients with erectile dysfunction (ED) after inflatable penile prosthesis implantation. Material and Methods: Forty-one patients who underwent to an inflatable penile prosthesis implantation surgery due to ED were included in the study. The age of the patients, the indications for surgery, and the type of prosthesis implanted were recorded. All patients were implanted two-piece inflatable (AMS Ambicor™) or three-piece inflatable (AMS 700™) prostheses. A 36-item short form (SF-36) was used to assess the life quality of patients. The scores obtained from these forms were recorded and used to compare the preoperative and postoperative quality of life of the patients. Results: The mean age of the patients was 59.9 (38–78) years. The mean follow-up was 25.1 (12–39) months. A three-piece inflatable penile prosthesis was implanted in 11 (26.8%) of the 41 patients and the others were implanted with a two-piece inflatable penile prosthesis. Average SF-36 scores were increased significantly after surgery in all groups. Conclusions: Inflatable penile prosthesis implantation is one of the most satisfactory treatment methods of ED and our study shows that with this treatment the patients can be provided a significant improvement in life quality.